Mechanical properties of extensive calcified costal cartilage: An experimental study. Issue 2 (February 2023) - Wang, Xin; Dong, Wenfang; Wang, Huan; You, Jianjun; Zheng, Ruobing; Xu, Yihao; Fan, Fei
Abstract: Background: Autologous costal cartilage is widely used as nasal augmentation or nasal reconstruction material. However, no study has focused on the mechanical difference between no calcified costal cartilage and extensive calcified costal cartilage at present. Our study aims to study the loading behavior of calcified costal cartilage under tensile and compressive stress. Method: Human costal cartilage specimen was obtained from five extensive calcified costal cartilage patients and classified into four groups (group A: no calcified costal cartilage; group B: calcified costal cartilage; group C: no calcified costal cartilage after transplantation in BALB/c nude mice for half a year; group D: calcified costal cartilage after transplantation in BALB/c nude mice for half a year). Young's modulus, stress relaxation slope, and relaxation amount were analyzed through tensile and compressive tests using a material testing machine. Results: We included five female patients with extensive calcified costal cartilage. Group B exhibited significantly higher Young's modulus in both the tensile and compressive tests (p < 0.05 in tensile test, p < 0.01 in compressive test), higher relaxation slope (P < 0.01) and higher relaxation amount (p < 0.05 in compression test). After transplantation, the Young's modulus of calcified and non-calcified costal cartilage decreased, except that the calcified costal cartilage increased slightly in the tensile test. The final relaxation slope and relaxation amount had increased at different degrees, but the changes did not change significantly before and after transplantation (P > 0.05). Conclusion: Our results showed that the stiffness of calcified cartilage would increase 30.06% under tension and 126.31% under compression. This study may provide new insights to researchers focusing on extensive calcified costal cartilage can be used for autologous graft material.